Pakistán: Musharraf en la encrucijada - Priego Moreno, Alberto (UNISCI Discussion Papers, 2007)
Pakistan is living a very instable period. President Musharraf maintains differences with several ethnic minorities, with the army and overall with the principal Islamist groups. Indeed, the International Community has put pressure on President Musharraf who is being demanded for democratic reforms. There are four big challenges that Musharraif need to face if he wants Pakistan not to become a Rogue State: democratization, poverty reduction, controlling Islamic radicalism and improving its relations with India.